2015
DOI: 10.1007/s00384-015-2133-x
|View full text |Cite
|
Sign up to set email alerts
|

“Core out” or “curettage” in rectal advancement flap for cryptoglandular anal fistula

Abstract: The core-out technique causes a significant decrease in squeeze pressures, which reflects damage to the external anal sphincter. This could lead to incontinence in high-risk patients. Curettage is a simple technique that preserves the values of squeeze pressures without increasing recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Study and patient characteristics are shown in Table S1 (supporting information) , . Five studies were RCTs, six were prospective cohort studies and 19 were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Study and patient characteristics are shown in Table S1 (supporting information) , . Five studies were RCTs, six were prospective cohort studies and 19 were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…And mild to moderate incontinence occurred in 35% of the patients after operation. Anorectal pressure measurements showed that resting pressure and systolic pressure decreased [21]. In a retrospective analysis, Data are mean (SD) or number (%).…”
Section: Discussionmentioning
confidence: 99%
“…So it is recommended for the treatment of fistula-in-ano by American Society of Colon and Rectal Surgeons (ASCRS) and Italian Society of Colorectal Surgery (Società Italiana di Chirurgia Colo-Rettale, SICCR) (Strong recommendation based on moderate-quality evidence, 1B) [ 3 , 23 ]. Although the sphincter is not been incised, it is still reported that 13.2% of patients with CPAF suffer from mild to moderate incontinence in a systematic review, and anorectal manometry found that the anal canal resting pressure and anal canal squeeze pressures are decreased postoperatively [ 3 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%